CDF modelling for the optimum tilt and azimuth angle for PV installations: case study based on 26 different locations in region of the Yorkshire UK. Issue 3 (10th December 2018) - Dhimish, Mahmoud; Mather, Peter; Holmes, Violeta; Sibley, Martin
Abstract : The optimum tilt and azimuth angle for PV installations in 26 different locations within the county of Yorkshire, UK have been evaluated. In order to examine the performance of the PV systems, a selection of criteria has been identified as follows: (i) the maximum difference in the age of the PV installations is no older than two years, (ii) PV modules technology is crystalline‐Silicon (c‐Si), (iii) maximum area of study in each location is 20 km 2, and (iv) PV systems have either the same tilt or azimuth angle within ±2°. The Huddersfield area was used as the primary example to evaluate the proposed methodology. The optimum tilt and azimuth angle for PV installations in the area is 39° and −1° respectively. Moreover, based on 4 kWp PV installations observed in all studied locations, a geographical map representing the annual energy production in the 26 locations has been drawn. The maximum annual energy production is observed for the city of Hull, whereas the minimum observed for the town of Keighley. Finally, the evaluation of the overall annual energy production is discussed using the analysis of the direct normal irradiance (DNI), ambient temperature, air frost, and the cloudiness.